Evaluasi Total Quality Management pada SMP Islam Athirah 1 Kajaolalido Kota Makassar - Haerul Amri; Patta Bundu (Madrasah Tsanawiyah DDI Cilellang, 2021)
This study aims to evaluate the implementation of Total Quality Management (TQM) at SMP Islam Athirah 1 Kajaolalido in Makassar city on aspects of the plan, implementation, and achievement. The study is a qualitative approach with an evaluation type. The subjects of the study were the director, the principal, and the teacher of SMP Islam Athirah 1 Kajaolalido in Makassar city. Data were collected by employing interview, observation, and documentation. Based on the evaluation being implemented, the assessors concluded that: 1) in arranging the plan, SMP Islam Athirah 1 Kajaolalido in Makassar city had implemented TQM characteristics; 2) in the implementation aspect, SMP Islam Athirah 1 Kajaolalido in Makassar city had implemented TQM characteristics as well basically; 3) in achievement aspect, SMP Islam Athirah 1 Kajaolalido in Makassar city had achieved the objectives of the implementation of TQM. It can be seen from various academic and non-academic achievements obtain by the students. Moreover, the level of satisfaction from the parents as the external customers has also improved. However, teachers as the internal customers have yet to obtained significant impact from the implementation of TQM in SMP Islam Athirah 1 Kajaolalido in Makassar city.